Effect of SnO–P2O5–MgO glass addition on the ionic conductivity of Li1.3Al0.3Ti1.7(PO4)3 solid electrolyte. Issue 1 (1st January 2022) - Kang, Jingrui; Gu, Rui; Guo, Xu; Li, Jing; Sun, Hongchen; Zhang, Leiyang; Jing, Ruiyi; Jin, Li; Wei, Xiaoyong
Abstract: NASICON-type structured compounds Li1+ x M x Ti2- x (PO4 )3 (M = Al, Fe, Y, etc.) have captured much attention due to their air stability, wide electrochemical window and high lithium ion conductivity. Especially, Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) is a potential solid electrolyte due to its high ionic conductivity. However, its actual density usually has a certain gap with the theoretical density, leading the poor ionic conductivity of LATP. Herein, LATP solid electrolyte with series of SnO–P2 O5 –MgO (SPM, 0.4 wt%, 0.7 wt%, 1.0 wt%, 1.3 wt%) glass addition was successfully synthesized to improve the density and ionic conductivity. The SPM addition change Al/Ti–O bond and P–O bond distances, leading to gradual shrinkage of octahedral AlO6 and tetrahedral PO4 . The bulk conductivity of the samples increases gradually with SPM glass addition from 0.4 wt% to 1.3 wt%. Both SPM and the second-phase LiTiPO5, caused by glass addition, are conducive to the improvement of compactness. The relative density of LATP samples increases first from 0 wt% to 0.7 wt%, and then decreases from 0.7 wt% to 1.3 wt% with SPM glass addition. The grain boundary conductivity also changes accordingly. Especially, the highest ionic conductivity of 2.45 × 10 −4 S cm −1, and a relative density of 96.72% with a low activation energy of 0.34 eV is obtained in LATP with 0.7 wt% SPM. Increasing the density of LATP solid electrolyte is crucial to improve the ionic conductivity of electrolytes and SPM glass addition can promote the development of dense oxide ceramic electrolytes.